1997
DOI: 10.1046/j.1365-2842.1997.00452.x
|View full text |Cite
|
Sign up to set email alerts
|

Condylar determinants in a patient population: electronic pantograph assessment

Abstract: Posterior condylar determinants play a key role in the establishment of a stable and harmonious occlusal scheme. Various methods exist to record the posterior condylar factors. The Denar electronic pantograph computes these condylar determinants automatically after the execution of a pantographic tracing. Research has validated the accuracy and reliability of this electronic pantograph. Electronic pantographic analysis was carried out on 55 patients referred for various prosthodontic consultations. Values for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 17 publications
1
17
0
2
Order By: Relevance
“…[145] If the individual inclination of the articular eminence is very steep or flat, guidance derived from the mean value settings may vary sufficiently leading to incorporation of inaccuracies while accomplishing a particular clinical objectives such as posterior disocclusion or balanced occlusion. [67] Various intra-oral and extra-oral methods have been used to register the path of the condyle and adjust the articulator accordingly.…”
Section: Introductionmentioning
confidence: 99%
“…[145] If the individual inclination of the articular eminence is very steep or flat, guidance derived from the mean value settings may vary sufficiently leading to incorporation of inaccuracies while accomplishing a particular clinical objectives such as posterior disocclusion or balanced occlusion. [67] Various intra-oral and extra-oral methods have been used to register the path of the condyle and adjust the articulator accordingly.…”
Section: Introductionmentioning
confidence: 99%
“…On jaw-closing, the incisor region typically laterodeviates about 5 mm, then moves medially as the food bolus engaged (Ahlgren, 1976;Gibbs and Lundeen, 1982;Miller, 1991). The mandibular condyles' lateral translation is minimal (0.4-0.6 mm) during chewing and other tasks (Gibbs and Lundeen, 1982;Payne, 1997;Okano et al, 2002;Otake et al, 2002;Miyawaki et al, 2004;Huang et al, 2006). During bolus compression therefore, the jaw rotates around its ipsilateral condyle as the contralateral condyle returns to its articular fossa (Gibbs and Lundeen, 1982;Gallo et al, 2000Gallo et al, , 2006Palla et al, 2003;Gallo, 2005;Miyawaki et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…As jaw biomechanics are difficult to study directly, modelling has become an important investigative tool (van Eijden, 2000;Koolstra, 2002;Hannam, 2005;Koolstra and van Eijden, 1995, 1997, 2005Peck and Hannam, 2007;van Eijden and Koolstra, 1998;Peck et al, 2000Peck et al, , 2002Sanguineti et al, 1998;Hansma et al, 2006;Stavness et al, 2006;Leon et al, 2006;de Zee et al, 2007). Simulations of the chewing cycle are rare however.…”
Section: Introductionmentioning
confidence: 99%
“…In the present investigation, mean inclination of the first condylar movement sequence showed 45.9u (SD 10.1) for the left joint, and 46.8u (SD 10.2) for the right joint, in reference to Camper's plane (around 60.9 and 61.8u with the Frankfort horizontal as the reference plane). Those values represent the upper limit of the reported values 5,14,17,19,20,24,25,27,28,[32][33][34] for condylar inclination. Review of the literature shows large variations in obtained condylar inclination values.…”
Section: Discussionmentioning
confidence: 85%
“…24,25 Additional advantages of electronic axiography is avoidance of radiation exposure and real-time threedimensional representation of mandibular movements. 26 Most of the studies that observed TMJ anatomy and function used one specific sagittal condylar inclination angle 14,17,19,27,28 describing the left and right joints. Existing data about intraindividual variations of the sagittal condylar path are scarce.…”
Section: Introductionmentioning
confidence: 99%